Thermal performance evaluation of a diamond-shaped roughened tube - Chokphoemphun, Suriya; Kamma, Panit; Promvonge, Pongjet; Promthaisong, Pitak (My University, 2025)
Thermal performance evaluation was examined numerically in a diamond-shaped roughened tube, which created recirculation and pair counter-rotation flows, which helped to disrupt the boundary layer, and increased fluid mixing led to improving the rate of heat transfer. The parameters studied, including relative depth ratio, e/D, DR, from 0.02 ≤ DR ≤ 0.14, and relative pitch ratio, p/D, PR, from 0.25 ≤ PR ≤ 1.5, under turbulent flow conditions, 3000 ≤ Re ≤ 20,000. Computed results included heat transfer (Nu/Nu0), frictional loss (f/f0) and thermal performance (in terms of thermal enhancement factor, TEF). The simulations showed that the velocity and heat transfer became fully developed periodic at around x/D ≈ 6–7.5. The pair counter-rotation flows increased the level of both the flow strength and the mixing of fluid, and disrupted the boundary layer, leading to an increase in heat transfer rate. The Nu/Nu0, f/f0 and TEF were achieved in a range of 1.00–3.34, 1.21–24.00 and 0.69–1.56. The maximum TEF was found at 1.56 for DR = 0.08, PR = 0.50 and Re = 5000.
Keywords: Diamond-shaped roughened tube; Frictional loss; Heat transfer; Thermal performance; Turbulent flow